4 - Éléments pour une critique de la planification macro-économique du développement dans les pays africains - Makhtar Diouf, (Africa Development, 1982)
Makhtar DIOUF's paper deals with a criticism of the Macro- Makhtar DIOUF's paper deals with a criticism of the Macro- economic Planning of Development in African countries . According to the author this type of planning - perceived as a « Voluntarist approach to supply scant resources as much as possible to meet ever - arising needs» - has failed in African experiences of development. He argues that this failure stems from an inappropriate approach to economic development and an ertoneous planning development as synonymous with economic growth and as a result, as a mere increase of per capita income; and from the methodological point of view, development as it was planned did not bring about any real economic development because not only did the plans worked out heretofore in Africa stem from the colonial plans of the 1950s, but they were always drawn up by European or American technical assistants whose standards and concepts of development were different from the concerns of African masses. Moreover, the statistical data used was collected through very unreliable techniques of economic projections. In addition to these technical reasons, there are political ones which give the plan not only an economic objective -that of supplying a market study to foreign interests - but also an internal political function - that of mysti- fying populations in so far as African public authorities consider it essential that national Assemblies accept the text of the plan and pass it without any discussions. The author finally concludes that what is needed in Africa is regional and local planning through small projects (wells, classrooms, dispensaries and maternities, etc.) such as the one currently being experimented in Senegal. Makhtar DIOUF, Faculté des Sciences Juridiques et Economiques, Université de Dakar , Sénégal.